PENANGANAN RELIGIUSITAS SANTRI YANG MENGALAMI GANGGUAN KECEMASAN MELALUI TERAPI SHALAT DAN RUQYAH: SEBUAH STUDI KASUS [HANDLING OF RELIGIOUS STUDENTS WITH ANXIETY DISORDERS THROUGH PRAYER AND RUQYAH THERAPY: A CASE STUDY] - Wifaqul Azmi; C Casmini (Journal of Contemporary Islamic Counselling, 2022)
This study aims to link religiosity with anxiety disorders, and to use the spirituality of a santri to deal with his anxiety so that he can change irrational thoughts, feelings and negative behavior into something positive. This study uses the ruqyah counseling method and prayer therapy. Participants who have liver disease and anxiety disorders that cause participants to experience negative changes in themselves, turn into individuals who have positive behavior and more rational thinking. The research carried out includes qualitative research with the case study method (case studies). The focus of this research is on the Asy-Syakiroh Islamic Boarding School, and the participants who participate are permanent students who are in the Asy-Syakiroh Islamic Boarding School. The changes that occurred in the two participants were the result of prayer and ruqyah therapy that had been given in general, they could change irrational thoughts, negative heart content and negative behavior, turning into individuals who have positive behavior and more rational thinking. The process of change that occurred in the two participants was seen not only based on the participant's acknowledgment, but from the observations of researchers and therapists, also based on the therapist's evaluation during the therapy process until the follow-up period.